Grafting of styrene onto polyethylene in near critical media - Martini, Raquel Evangelina (2011)
In the present work, near critical n-heptane is used as reaction medium for the copolymerization of polyethylene with styrene monomer, using alkylation reaction with different amounts of aluminum chloride (AlCl3) as catalyst. In this way, polyethylene chains will be more available to react with the catalyst. The reaction effect on pure reactants, as well as, the catalyst activity was previously investigated.The reaction occurrence was corroborated by analyzing the reaction products before and after careful polystyrene extraction with tetrahydrofuran. The reaction products were characterized by Fourier Transform Infrared Spectroscopy, Nuclear Magnetic Resonance, Scanning Electron Microscopy, Transmission Electron Microscopy, Differential Scanning Calorimetry and Size Exclusion Chromatography. The possible architecture for the copolymer molecule was proposed from the molecular characterization results. On the other hand, the polystyrene grafting modifies final properties of polyethylene, increasing the oxygen barrier properties without deteriorating significantly the mechanical properties of the films. In this sense this reaction seems to be a promising route to modify PE films in order to increase the barrier properties.